A Thyroid Case for Year-One Medical Students - Dapinderjit Gill; Mary Moore; Kal Winston; Niels Larsen; Aidi Yin; Diana Callender; Valarie Thomas (Association of American Medical Colleges, 2014)
Abstract During the first year of medical school, students are exposed to the thyroid in many different domains such as anatomy, histology, endocrinology, physiology, and pathology. In order to bring all the information from the multiple disciplines together, faculty from various departments designed a problem-based learning (PBL) case using a fictional patient with Graves' disease. The key element, taken from a PBL design, is that students work in small groups and identify (1) what they already know, (2) what they need to know and, (3) how and where to access new information to solve the problem. The case involves a fictional patient, named Dr. Oscarsson, who presents with thyrotoxicosis. The case is designed to run in groups of eight to nine students in three sessions with one facilitator. The first session is expected to last 1 hour, the second session 2 hours, and the third session 1 hour. During the first two sessions, the case information is progressively disclosed. During the third session, the epilogue and case objectives of the activity are distributed. Before starting this case, students must be introduced to the SGL process and the method of extracting relevant data, analysis of the data, creating hypotheses, and identifying learning issues which may arise from discussion. Students are asked to research the learning issues outside the session and return to the next session prepared to present their findings to the group. Among the issues raised in this case are issues of thyroid function, hyperthyroidism, autoimmune diseases, Graves' disease, treatment of Graves' disease, and use of evidence-based medicine. The facilitator version contains prompts which help facilitators guide students to particular learning goals.